Artificial Intelligence in English Language Education: Advancing SDG 4 and Institutional Excellence through Secondary Data Analysis - Liliura, Deemimah; Apristia, Dr. Lelu Dina (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Artificial Intelligence (AI) has become a new feature of modern education, transforming the teaching and learning process worldwide. Although AI has grown in use in English language teaching via chatbots like ChatGPT, grammar assistants like Grammarly, and other intelligent tutoring systems, its relationship with the global education agenda, especially Sustainable Development Goal 4 (SDG 4), has not been studied extensively. Closing this gap, this paper examines how AI can be used in the development of English language education and how it can contribute to SDG 4 and institutional excellence. The study utilized a secondary data model, based on bibliometric and literature-based reviews of Scopus, Web of Science, and selected policy reports published between 2015 and 2025. Results indicate that following 2020, AI-related publications increased rapidly, which is a clear indication of the shift towards more pedagogical applications rather than technical applications, and the development of international collaboration between AI, language learning, and SDG 4. The literature review suggests that AI can positively impact EL learning, but also highlights significant concerns about cheating, discrimination, and privacy invasion. Such discussions enable this paper to present the argument that AI may become a transformative tool in learning the English language and institutional growth, subject to how AI can be influenced by ethically just and policy-based paradigms. These results demonstrate what policy-makers, institutions, and educators can do to facilitate the intended use of AI so as to be in a position to achieve inclusive, quality, and sustainable educational development.